OCEANOGRAPHIC DATA OF THE 24TH JAPANESE ANTARCTIC RESEARCH EXPEDITION FROM NOVEMBER 1982 TO APRIL 1983 - ハンザワ, タカシ; イワモト, コウジ; HANZAWA, Takashi; IWAMOTO, Koji (National Institute of Polar Research, 1984)
P(論文) This report presents the data of the oceanographic observations on board the icebreaker Fuji and the tidal observation at Syowa Station, which were carried out in the summer mission of the 24th Japanese Antarctic Research Expedition in 1982-1983. departmental bulletin paper